Cytological Method of Barr Body Expression in Dental Pulp Tissue at Varying Temperature - Ambika Murugesan; Sekar Balakrishnan; Indra Priyadharshini Kumaresan; Arun Jayakumar; Jayashree Mohan; Bharath Champakesan (Wolters Kluwer Medknow Publications, 2018)
Introduction: Natural disasters in large population need major attention in person identification. It can be performed by means of simple techniques that are easier to use. Aim: To identify the Barr body in female dental pulp by cytological method, after exposing at varying temperature. Objective: The expression of Barr bodies was compared among different age groups, various temperature, and two types of stain. Materials and Methods: Teeth obtained from 60 female individuals were divided into two groups based on their age. In each group, 30 teeth were exposed at three different temperatures (200°C, 300°C, and 400°C), 10 teeth in each temperature. The pulp tissue obtained from teeth was centrifuged and stained with hematoxylin and eosin (H&E) and Papanicolaou stain (PAP). Presence of visible sex chromatin in the nuclear periphery was considered positive for Barr chromatin test. The results obtained were analyzed by both descriptive analysis and independent t-test. Result: The peripherally condensed Barr body in hyperchromatic nuclear outline was clearly visible in younger individuals at 200°C and is more accurately expressed in H&E stain. Conclusion: In our study, based on the results obtained from the smear of pulp tissue, expression of Barr bodies' decreases as age and temperature increases. Further study with increase in sample size is mandatory to confirm the above conclusion.